Index of Authors and Scholars - The Editors, - (Nordic Archaeological Abstracts - NAA, 2021)
For practical reasons the alphabet employed is abc ... u v w x y (ii) z å (aa) li (æ) o ( ø). Finnish names beginning with aa will, however, be alphabetized as beginning with a double a. German li, o and il will be treated as Nordic å o and y. I and j, v and w are separated. lcelandic d and p are equivalent to d and th. The Cyrillic alphabet is transliterated according to the international system for the transliteration of Cyrillic characters (ISO].